2021
DOI: 10.1089/dia.2021.0110
|View full text |Cite
|
Sign up to set email alerts
|

A Worldwide Perspective on COVID-19 and Diabetes Management in 22,820 Children from the SWEET Project: Diabetic Ketoacidosis Rates Increase and Glycemic Control Is Maintained

Abstract: To investigate the short-term effects of the first wave of COVID-19 on clinical parameters in children with type 1 diabetes (T1D) from 82 worldwide centres participating in the SWEET registry.Methods: Aggregated data per person with T1D ≤ 21 years of age were compared between May/June 2020 (first wave), August/September 2020 (after wave) and the same periods in 2019. Hierarchic linear and logistic regression models were applied. Models were adjusted for gender, age-and diabetes duration-groups. To distinguish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 29 publications
3
24
1
2
Order By: Relevance
“…This finding suggests that the delay in diagnosing type 1 diabetes is not the only cause for an increased risk of DKA. This result might also be supported by the reported no-change or unexpected lower HbA1c levels during the pandemic ( 25 , 28 ). That said, a limitation does exist regarding the duration of symptoms given that the information provided in the studies depends on parents’ ability to recall those symptoms.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This finding suggests that the delay in diagnosing type 1 diabetes is not the only cause for an increased risk of DKA. This result might also be supported by the reported no-change or unexpected lower HbA1c levels during the pandemic ( 25 , 28 ). That said, a limitation does exist regarding the duration of symptoms given that the information provided in the studies depends on parents’ ability to recall those symptoms.…”
Section: Discussionsupporting
confidence: 59%
“…showed no difference in DKA cases in those with preexisting type 1 diabetes ( 34 ). Although some studies have reported a decrease in physical activities during the lockdown period ( 25 , 41 ), many studies have observed good glycemic control during the lockdown period, which might be a result of close parental supervision during the lockdown or the increased use of diabetes-related technology in some countries ( 25 , 42 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Die COVID-19-Krise führte weltweit zu Störungen der Routinen in der ambulanten und stationären klinischen Versorgung [9,14,30]. In der gegenwärtigen COVID-19-Pandemie sind Familien von Kindern mit Diabetes besonders auf ihre Diabetestechnologie und Unterstützung durch ihre Diabetesteams angewiesen.…”
Section: Telemedizin In Der Kinderdiabetologieunclassified
“…1 , 2 A higher incidence of diabetic ketoacidosis (DKA) and especially severe forms have been observed during the COVID‐19 pandemic. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Diabetic ketoacidosis is a serious but avoidable complication of type 1 diabetes that can be triggered by viral infections. 3 It has a mortality of 0.3%–0.5% in wealthy countries and considerably higher in developing nations (approximately 10%). 3 Electrolyte abnormalities such as hypokalemia and hypernatremia can emerge during DKA and lead to significant morbidity, but they are relatively rare at presentation, before the initiation of therapy.…”
Section: Introductionmentioning
confidence: 99%